Orthopaedics in era of Computers and Internet - Dr Saurabh Jain (Orthopaedic Journal of M. P. Chapter, 2018)
Today, computers are a part of our life & have changed the way we live and the way we practice medicine. Their qualities as user friendly, cheap, availability, time saving, multitasking, documentation, and knowledge update has helped in opening up a lot of possibilities for their application in the medical field.